Cytokine Responses in Gills of Capoeta umbla as Biomarkers of Environmental Pollution - Danabas, Durali; Yildirim, Nuran Cikcikoglu; Yildirim, Numan; Onal, Ayten Oztufekci; Uslu, Gulsad; Unlu, Erhan; Tayhan, Nilgun (Wiley, 2016)
Immunological biomarkers reflect the effects of exposure to environmental contaminants. In this study, the suitability and sensitivity of cytokine responses, interleukin 1 beta (IL-1 beta), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha) in gill tissues of Capoeta umbla (Heckel, 1843), collected from different regions, as early warning indices of environmental pollution and ecosystem health was evaluated. Fish and water samples were taken from ten stations in March and September 2011 and 2012. Tumor necrosis factor-alpha, IL-1 beta and IL-6 levels were determined in samples of the gill tissues by using an ELISA kit. Significant variations of TNF-alpha, IL-1 beta and IL-6 levels observed between stations and seasons. The results of this study show that seasonal variations of cytokine responses in gills of Capoeta umbla are sensitive to the contaminants present in Uzuncayir Dam Lake (Tunceli, Turkey) water and are valuable biomarkers for environmental pollution and ecosystem health.
Keywords: Uzuncayir Dam Lake; fish; cytokine; gills